Numerical investigation on laminar slot-jet impinging in a confined porous medium in local thermal non-equilibrium. (July 2016) - Buonomo, Bernardo; Lauriat, Guy; Manca, Oronzio; Nardini, Sergio
Highlights: Confined single slot jet impinging in high permeability porous medium is investigated. Opposite wall to slot jet is partially heated at uniform heat flux. Brinkman–Forchheimer–Darcy model and local thermal non-equilibrium are assumed. For low Peclet numbers average Nusselt number decreases due to the buoyancy. Porosity effects on the average Nusselt numbers were found weak. Abstract: A numerical investigation on a single slot jet impinging in a porous parallel-plate channel containing an air-saturated, high permeability porous medium is accomplished. The wall opposite the slot jet is partially heated at uniform heat flux and the buoyancy effects are taken into account. The fluid flow is assumed two dimensional, laminar and steady. The porous medium is modeled using the Brinkman–Forchheimer-extended Darcy model and the Boussinesq approximation. The local thermal non-equilibrium (LTNE) hypothesis is invoked. The results are discussed in terms of streamlines, fluid and solid phase temperature fields, wall temperature profiles and local and average Nusselt numbers. The porous medium allows a more significant heat transfer close to the end of the heated part of the plate. For low Peclet numbers, forced flow and natural convection are opposite and the mean Nusselt number shows a decrease in heat transfer, whereas they are aiding for high Peclet numbers. Porosity effects on the average Nusselt numbers were found weak.